2013
DOI: 10.1177/1464884913501836
|View full text |Cite
|
Sign up to set email alerts
|

Playing a crusader role or just playing by the rules? Role conceptions and role inconsistencies among environmental journalists

Abstract: Environmental journalists have historically struggled between journalistic objectivity and environmental advocacy. But the roles they embrace are based not only on their individual conceptions but also on their perceptions of what their organizations expect from them. Thus, journalistic role conceptions are the melding of individual and organizational role conceptions. These roles do not always correspond, especially for environmental journalists who must compete for space and attention with more sensational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…This is problematic because several recent studies have indicated that the actual role performance of journalists often differs from their role conceptions, as stated in surveys, interviews and codes of conduct (Mellado et al, 2017;Tandoc et al, 2013). Moreover, research has long recognised that journalists regularly face conflicting expectations from their surrounding environment and must find ways to negotiate between and combine multiple roles in their work (Hanitzsch & Vos, 2018;Hellmueller & Mellado, 2015;Kramp & Weichert, 2014;Rosten, 1937;Tandoc & Takahashi, 2014).…”
Section: A Social-interactionist View On Journalists' Role Conceptionsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is problematic because several recent studies have indicated that the actual role performance of journalists often differs from their role conceptions, as stated in surveys, interviews and codes of conduct (Mellado et al, 2017;Tandoc et al, 2013). Moreover, research has long recognised that journalists regularly face conflicting expectations from their surrounding environment and must find ways to negotiate between and combine multiple roles in their work (Hanitzsch & Vos, 2018;Hellmueller & Mellado, 2015;Kramp & Weichert, 2014;Rosten, 1937;Tandoc & Takahashi, 2014).…”
Section: A Social-interactionist View On Journalists' Role Conceptionsmentioning
confidence: 99%
“…Journalists perform a particular role in social interaction wherein "they anticipate the consequences of their reporting to others and the social context" (Hellmueller & Mellado, 2015, p. 6). This perspective adds a fair amount of malleability, negotiability and context-dependence to journalistic roles (Tandoc & Takahashi, 2014). Journalists may both perceive and enact their roles quite differently according to the topic they are covering, the kind of sources they are engaged with when reporting on the issue and the perceptions they have about the broader societal context.…”
Section: A Social-interactionist View On Journalists' Role Conceptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This extant research highlights shortcomings in the reporting, such as lack of accuracy in scientific reporting, bias in the use of sources, struggles in balancing objectivity and advocacy, and the individual and structural factors that affect the reporting (Palen, 1999;Detjen et al, 2000;Sachsman et al, 2005;Crow and Stevens, 2012;Tandoc and Takahashi, 2014b). In addition, environmental and science reporters are experiencing changes in their perceived societal roles, especially within online news production (Fahy and Nisbet, 2011;Tandoc and Takahashi, 2014b). Fahy and Nisbet (2011) suggest that science journalists should take on the roles of knowledge brokers or information curators to differentiate themselves from other information producers (e.g., blog writers, scientists, and public relations professionals).…”
Section: Problems and Challenges In The Practice Of Environmental Joumentioning
confidence: 99%